Eluxadoline Versus Antispasmodics in the Treatment of Irritable Bowel Syndrome: An Adjusted Indirect Treatment Comparison Meta-analysis - Qin, Di; Tao, Qing-Feng; Huang, Shi-Le; Chen, Min; Zheng, Hui (Frontiers in Pharmacology, 2022)
Objective: Eluxadoline is a newly-approved drug for irritable bowel syndrome (IBS), and it has rarely been compared with positive controls. We aim to compare eluxadoline with antispasmodics in the treatment of IBS. Methods: We searched OVID Medline, Embase, the Cochrane Central Register of Controlled Trials for randomized controlled trails (RCTs) that compared eluxadoline or antispasmodics with placebo. The search was performed from inception to September 1, 2020 without any language restriction. The primary efficacy outcome was relief of abdominal pain defined by pain scores were reduced by at least 30% from baseline. The secondary efficacy outcome was responder rate, defined by a composite response of decrease in abdominal pain and improvement in stool consistency on the same day for at least 50%. The data were pooled using a random-effects model. Efficacy and safety were compared between eluxadoline and antispasmodics, reported as a pooled relative risk (RR), and ranked by treatments according to their P-scores. Results: We included 42 RCTs from 45 articles (n=8457). After completion of treatment, drotaverine, pinaverium, alverine combined with simethicone (ACS) and eluxadoline 100mg were efficacious in relief of abdominal pain, and drotaverine ranked the first (RR, 2.71 [95% CI, 1.70-4.32], P-score =0.99); no difference was found between these treatments. After completion of treatment, drotaverine, otilonium, cimetropium, pinaverium and eluxadoline 100mg were efficacious in responder rate, and drotaverine ranked the first (RR, 2.45 [95%CI, 1.42 to 4.22], P-score=0.95); no difference was found between these treatments. Pinaverium was significantly more effective than eluxadoline in responder rate in sensitivity analysis (RR, 1.72 [95% CI, 1.33-2.21]). There is no significant difference in the number of adverse events for all interventions to placebo. Conclusions: Our network meta-analysis showed that antispasmodics were at least as effective as eluxadoline in relieving abdominal pain of IBS.